Vestibular Rehabilitation Telehealth During the SAEA-CoV-2 (COVID-19) Pandemic - Harrell, Regan G.; Schubert, Michael C.; Oxborough, Sara; Whitney, Susan L. (Frontiers in Neurology, 2022)
During the COVID-19 pandemic, physical therapists transitioned to provide telehealth in the United States. We sought to determine the experiences of physical therapists delivering telerehabilitation for vestibular disorders including barriers, preferences, and concerns. A survey was created using the results of a focus group and previously published studies. The survey was distributed across social media sites and through email- the link was sent to the orthopedic, neurologic, and geriatric academies of the American Physical Therapy Association list serves. The email was also shared with each of the 50 state chapters of the American Physical Therapy Association. The survey was broken down into five sections: demographic information, physical therapists’ general impressions of telehealth, physical therapists’ comfort level treating various vestibular diagnoses, and common barriers physical therapists experienced during telehealth sessions. There were 159 completed surveys. More than 80% of physical therapists surveyed agreed that telehealth was an effective platform for vestibular physical therapy. When asked whether physical therapists felt the patient had similar health outcomes with telehealth versus clinic care 68% of physical therapists agreed. For the physical therapists who treated posterior or horizontal canal benign paroxysmal positional vertigo via telehealth, more than 50% were comfortable treating these conditions via telehealth. In analyzing common peripheral vestibular diagnoses treated via telehealth including bilateral vestibular loss, Meniere’s disease, and vestibular neuritis more than 75% of the physical therapists reported comfort treating these diagnoses. Similarly, more than 75% of physical therapists who treated central vestibular diagnoses- including mild traumatic brain injury and vestibular migraine- via telehealth reported being comfortable treating these diagnoses. Physical therapists reported several barriers to tele healthcare ranging from concerns about testing balance with no caregiver present (94%) to challenges with providing a written home exercise program (33%). Physical therapists report that telehealth is a viable mechanism for providing rehabilitation for persons with balance and vestibular disorders. For common diagnoses, most physical therapists were comfortable treating vestibular disorders via telehealth. While barriers remain including maintaining patient safety and being able to complete a thorough vestibular exam, telehealth for vestibular physical therapy services holds promise for the delivery of virtual care.